Simplified FDTD Formulations for Magnetostatic Biased Graphene Simulations - Ramadan, Omar (IEEE-Inst Electrical Electronics Engineers Inc, 2020)
Simplified finite difference time domain (FDTD) formulations are presented for magnetostatic biased graphene simulations. In this respect, graphene's anisotropic conductivity is incorporated into the FDTD algorithm by using the second-order Runge-Kutta (RK) scheme with the minimal additional computational resources. Moreover, the complex frequency shifted perfectly matched layer is combined with the presented RK-FDTD formulations to model open-space graphene structures. Numerical tests are included to validate the given formulations
Keywords: Graphene; Time-domain analysis; Mathematical model; Magnetic domains; Finite difference methods; Perpendicular magnetic anisotropy; Complex-frequency shifted perfectly matched layer (CFS-PML); finite difference time domain (FDTD); magnetostatic biased graphene; second-order Runge– Kutta (RK) scheme